Global financial crisis, ownership structure and firm financial performance: An examination of listed firms in Australia - Saleh, A.; Halili, E.; Zeitun, R.; Salim, Ruhul (2017)
Purpose: This paper aims to investigate the financial performance of listed firms on the Australian Securities Exchange (ASX) over two sample periods (1998-2007 and 2008-2010) before and during the global financial crisis periods. Design/methodology/approach: The generalized method of moments (GMM) has been used to examine the relationship between family ownership and a firm’s performance during the financial crisis period, reflecting on the higher risk exposure associated with capital markets. Findings: Applying firm-based measures of financial performance (ROA and ROE), the empirical results show that family firms with ownership concentration performed better than nonfamily firms with dispersed ownership structures. The results also show that ownership concentration has a positive and significant impact on family- and nonfamily-owned firms during the crisis period. In addition, financial leverage had a positive and significant effect on the performance of Australian family-owned firms during both periods. However, if the impact of the crisis by sector is taking into account, the financial leverage only becomes significant for the nonmining family firms during the pre-crisis period. The results also reveal that family businesses are risk-averse business organizations. These findings are consistent with the underlying economic theories. Originality/value: This paper contributes to the debate whether the ownership structure affects firms’ financial performance such as ROE and ROA during the global financial crisis by investigating family and nonfamily firms listed on the Australian capital market. It also identifies several influential drivers of financial performance in both normal and crisis periods. Given the paucity of studies in the area of family business, the empirical results of this research provide useful information for researchers, practitioners and investors, who are operating in capital markets for family and nonfamily businesses.